KEGIATAN MARTIKULASI UNTUK PENGUATAN KEMAMPUAN MATEMATIKA SISWA SMP NEGERI 2 TANJUNG MORAWA - Antonius KAP Simbolon (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
The purpose of the matriculation activity is to improve the basic math skills of junior high school students so that when the learning process in the next material does not experience difficulties. The method used in this activity is through a pretest, providing material and practice questions, a posttest, and the final evaluation of the activity. The results of this activity are the basic understanding of students by 46.87%, and the final result of students who pass the minimum criteria of 53.13%.